2016
DOI: 10.1080/13625187.2016.1234597
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of first-generation women and girls with female genital mutilation in the European Union, Norway and Switzerland

Abstract: For the first time, scientific evidence gives a reliable estimate of the number of first-generation women and girls in Europe coming from countries where FGM is practiced. The use of census data proves reliable for policy makers to guide their actions, e.g., regarding training needs for health workers who might be confronted with women who have undergone FGM, or the need for reconstructive surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 3 publications
0
57
0
Order By: Relevance
“…A study by Van Baelen et al based on demographic data from 2011 estimated that 7910 girls and women living in Denmark had been subjected to FGM before immigration [ 4 ]. The current prevalence of girls and women having been, or in risk of being, submitted to FGM in Denmark is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Van Baelen et al based on demographic data from 2011 estimated that 7910 girls and women living in Denmark had been subjected to FGM before immigration [ 4 ]. The current prevalence of girls and women having been, or in risk of being, submitted to FGM in Denmark is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Due to migration over the past decades the practice of FGM has spread to European and other Western countries [ 3 10 ]. It has been estimated by the European Parliament that 500,000 women and girls have been subjected to FGM whereas 180,000 girls are in risk of being subjected to FGM [ 11 ]; though some argue that this is an under-estimation [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…[4] It may also be seen among some ethnic groups and immigrants living in developed European and North American countries and Australia. [5] Although there are no o cial and comprehensive statistics on the prevalence of FGM/C in Iran, the results of few studies have shown that the prevalence of the practice varies by region and is mainly concentrated in the western and southwestern provinces (Hormozgan, Khuzestan, Bushehr, Kurdistan, and Kermanshah [6][7][8] which are mostly inhabited by Sunni Muslims. The prevalence of the FGM/C is reported to be between 55.5 and 70% primarily in rural of these areas.…”
Section: Introductionmentioning
confidence: 99%
“…FGC is largely seen as an African phenomenon but is also practised in several Middle Eastern and Asian countries (Alkhalaileh et al 2017;Rashid, Patil, and Valimalar 2009), even if attitudes and practices regarding FGC are changing (Van Bavel, Coene, and Leye 2017; Graamans et al 2018). Migration has turned FGC into a global phenomenon, with more than half a million cut women and girls living in Europe, for example (Van Baelen, Ortensi, and Leye 2016). The prevalence of FGC seems to have reduced after years of preventive campaigns, but progress towards eradication is slow.…”
Section: Introductionmentioning
confidence: 99%